Chronic Inflammation: A Common Promoter in Tertiary Lymphoid Organ Neogenesis - Luo, Shanshan; Zhu, Rui; Yu, Ting; Fan, Heng; Hu, Yu; Mohanta, Sarajo Kumar; Hu, Desheng (Frontiers in Immunology, 2019)
Tertiary lymphoid organs (TLOs) frequently develop locally in adults in response to non-resolving inflammation. Chronic inflammation derives the differentiation of stromal fibroblast cells towards lymphoid tissue organizer-like cells, which interact with lymphotoxin12+ immune cells. The interaction initiates lymphoid neogenesis by recruiting immune cells to the site of inflammation and ultimately leads to the formation of TLOs. Mature TLOs harbor segregated T cell zone, B cell follicles with the activated germinal center, follicular dendritic cells, and high endothelial venules, which architecturally resemble those in secondary lymphoid organs. Since CXCL13 and LT12 play key roles in TLO neogenesis, they might constitute potential biomarkers of TLO activity. The well-developed TLOs actively regulate local immune responses and influence disease progression, thereby being regarded as the powerhouses of local immunity. In this review, we recapitulated the determinants for TLOs development, with great emphasis on the fundamental role of chronic inflammation and tissue resident stromal cells for TLO neogenesis, hence offering the guidance for therapeutic interventions in TLO associated diseases.